Assessing the contribution of public capital to private production - Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Using time-series cross-section data from the manufacturing sector of the 11West German ?Bundesländer? (Federal States) from 1970 to 1996, I examine the impact of public capital on private production. My econometric analysis explicitly takes into account four of the most frequent specification issues in the context of time-series cross-section data analysis: serial correlation, groupwise heteroscedasticity, cross-sectional correlation and nonstationarity of data. For all approaches and tested specifications, I find that public capital is a significant input for production in the manufacturing sector. Moreover, I find that differences in public capital endowment can explain long-term differences in productivity across the Bundesländer. One tentative conclusion that can be drawn from this finding is that differences in public capital endowment might also explain a part of the still-existing productivity gap between manufacturing in East and West Germany. However, I emphasise that the existence of positive effects of public capital on private production is a necessary, but not a sufficient condition for concluding that public investments should be boosted in the future.
Keywords: 330; Infrastruktur; Wertschöpfung; Privatwirtschaft; Verarbeitendes Gewerbe; Produktionsfunktion; Schätzung; Deutschland